Kemmerer Lives! The Evolution of the Composition of the Central Bank Boards of Five Latin American Countries - Salas-Díaz , Ricardo José (Tiempo y economía, 2023)
This study examines the evolution of the composition of the boards of the central banks from Bolivia, Chile, Colombia, Ecuador, and Peru throughout the 20th century. Although the initial boards of those central banks were similar, they included representatives from different institutions, such as labor unions, bankers, business associations, and governments. Over eighty years, governments implemented several reforms that changed the composition of the boards , increasing the weight of business associations, while rapidly decreasing the participation of labor unions and bankers. In the 1960s and 1970s, government representatives took over the boards until the independence reforms of the late 1980s and early 1990s. Despite facing political turmoil and undergoing several restructurings, these five “Kemmerer” central banks evolved in parallel up to the new century.